Energy cost of rifle carriage in biathlon skiing - Rundell, K. W.; Szmedra, L. (Medicine & Science in Sports & Exercise, 1998)
The purposes of this study were to: 1) compare physiological measurements of biathletes roller skiing with and without rifle carriage, 2) compare energy cost of rifle carriage between women and men, 3) examine the relationship of cycle length and cycle rate to energy cost of rifle carriage, and 4) compare physiological measurements to calculated estimates of power requirements of rifle carriage.